JETSTREAM Atherectomy: A Review of Technique, Tips, and Tricks in Treating the Femoropopliteal Lesions - Shammas, Nicolas W. (Int J Angiol, 2014)
JETSTREAM (Bayer, Whippany, NJ) atherectomy is a highly effective rotational atherectomy device with active aspiration capacity approved in the United States to treat infrainguinal obstructive peripheral arterial disease. The technique in using the JETSTREAM is critical and relies on appropriate wire use, appropriate sizing, and speed in advancing the cutter as well as the use of fluoroscopic imaging and tactile and auditory senses. Using the right technique, the device appears to have a low rate of distal embolization and complications and results in high procedural success. We describe our own experience with the JETSTREAM device and the techniques used in our endovascular laboratory.